Repräsentative Kunstwerke aus dem deutschsprachigen Raum im DaF-Projektunterricht - Gorąca, Gabriela; Jourdy, Natascha (Glottodidactica, 2011)
Project is one of the most stimulating and motivating form of working in group, so therefore it should be considered as an important element of a FLT. To prove this statement, it was conducted a project with students of Applied Linguistics, whose main idea was connected with the description of an inside and outside perspective of the representative paintings from the German speaking countries. The results of this initiative were fertile for both, lecturer and students and they will be described in the presented paper.